VALIDITY OF DISASTER E-BOOK TO IMPROVE DISASTER LITERACY SKILLS AT JUNIOR HIGH SCHOOL - Maulana Rifqi Asshiddiqi; Mudmainah Vitasari; Lulu Tunjung Biru (JURNAL PENA SAINS, 2021)
Natural disasters in Indonesia constantly occur every single year and have adverse effects. In order to minimize those negative effects, it is crucially needed to increase disaster literacy in the society, which starts from the students. To improve disaster literacy, students must be assisted with teaching materials that focus on disaster material, such as disaster education e-books. Disaster education e-books are teaching materials that contain the vibration, waves, and disaster materials combined with a webbed integration model. This research aimed to measure the validity level of the developed disaster education e-book. The research method applied was research and development with the 4D development model proposed by Thiagarajan et al. (1974). However, this research did not reach the disseminating stage, so the development model used became a 3D model consisting of defining, designing, and developing stages.  Validation questionnaires were used to measure product validity, and these questionnaires were assessed by two expert lecturers and three science teachers. The development of teaching materials in the disaster education e-books form scored 81%, and it was categorized in the valid category. As a result, the disaster education e-book developed was valid for use at the junior high school level.